Reflexiones sobre el drawback y su efecto sobre las exportaciones - Duarte Cueva, Franklin (2011)
In several countries drawback is a tool for promoting non-traditional exports. However, this custom procedure can not be used by all producers-exporters companies because its use involves strict compliance of the conditions approved by customs law. In the peruvian case, the level of use of drawback is more intensive in certain industries, providing a support for the competitiveness of companies which should be strategically used.